2015
DOI: 10.5897/ajbr2014.0795
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of partially purified cysteine protease inhibitor from Tetracarpidium conophorum (African walnut)

Abstract: Cysteine protease inhibitors (CPIs) have been known to be present in a variety of seeds of plants, and have been intensively studied as useful tools for potential utilization in pharmacology. This study reports the isolation of CPI from Tetracarpidium conophorum by 65% ammonium sulphate saturation, followed by ion exchange chromatography; further purification was by gel filtration chromatography. The molecular weight of the partially purified protein inhibitor was analyzed by SDS-PAGE to be approximately 20 kD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…50 -70% ammonium sulphate precipitation of protease inhibitors from seeds of Helianthus annuus gave the highest yield and inhibitory effect when incubated with larva gut proteases [46]. 65% ammonium sulphate saturation of CPI that exhibited the maximum inhibitory effect has also been reported [47].…”
Section: Discussionmentioning
confidence: 92%
“…50 -70% ammonium sulphate precipitation of protease inhibitors from seeds of Helianthus annuus gave the highest yield and inhibitory effect when incubated with larva gut proteases [46]. 65% ammonium sulphate saturation of CPI that exhibited the maximum inhibitory effect has also been reported [47].…”
Section: Discussionmentioning
confidence: 92%
“…Also, CPIs have been researched and implicated in some disease conditions such as diabetes, cancer and neurodegenerative disorders among many others [19]. Plant cysteine protease inhibitors (CPIs) have therefore been studied extensively [2,9,20]. However, this study is the first at attempting to characterize CPI from A. muricata.…”
Section: Discussionmentioning
confidence: 99%
“…Several protease inhibitors extracted from plants have been reported to be more effective after precipitating with high ammonium sulphate concentration. Obayomiet al; [9] reported that 65% ammonium sulphate saturation of CPI exhibited the maximum inhibitory effect. Ashouriet al; [22], also reported that a 50-70% ammonium sulphate precipitation of protease inhibitors from seeds of Helianthus annuus produced the highest inhibitory effect (41.53%) when incubated with larva gut proteases.…”
Section: Purification Of Cysteine Protease Inhibitormentioning
confidence: 98%
See 1 more Smart Citation
“…Researchers have identified cysteine protease inhibitors as an important tool for the utilization in pharmaceutical industry due to their potent health benefits. Obayomi et al [76] purified cysteine protease inhibitors from Tetracarpidium conophorum which is competitively inhibit papain, a proteolytic enzyme that aids in digestion.…”
Section: Cysteine Protease Inhibitorsmentioning
confidence: 99%